Mathematical induction proofing: Procedural fluency reviewed from the creative thinking level of mathematics students - Annurwanda, Pradipta; Friantini, Rizki Nurhana (Jurnal Riset Pendidikan Matematika, 2022)
Creativity in performing mathematics proof was assumed to be directed by the procedural fluency. This article examines the procedural fluency in proof based on the students' creative thinking level of mathematics. Subjects were selected pusposively to join the test and interview as the main instruments. Of the 36 students who took the test, 5 students were selected appropriate at each level of creative thinking skills to be followed with interviews.. The data were analyzed following data condensation, data presentation, and conclusion withdrawal as suggested by Miles, Huberman, and Saldana (2014). The results showed that very creative, creative, and quite creative students could demonstrate procedural fluency because they could use mathematical induction proof procedures correctly and modify the procedure in the correct rules although less creative students lacked completeness in performing mathematical induction proof procedures. Students of the lower creativity groups had less procedural fluency because they were unlikely to understand the use of mathematical induction proof procedures and found difficulties to apply mathematical induction proof procedures properly or even no attempt was made to modify procedures to solve problems.